Short- and long-term outcomes following atrial fibrillation in patients with acute coronary syndromes with or without ST-segment elevation. Issue 7 (10th March 2008) - Lopes, R D; Pieper, K S; Horton, J R; Al-Khatib, S M; Newby, L K; Mehta, R H; Van de Werf, F; Armstrong, P W; Mahaffey, K W; Harrington, R A; Ohman, E M; White, H D; et al.
Abstract : Objective: To assess variables associated with the occurrence of atrial fibrillation (AF) and the relation of AF with short- and long-term outcomes and with other in-hospital complications in patients with acute coronary syndromes (ACS) with and without ST-segment elevation. Design: Pooled database of 120 566 patients with ST-segment elevation myocardial infarction (STEMI) and non-ST-segment elevation (NSTE) ACS enrolled in 10 clinical trials. Multivariable logistic regression and Cox proportional hazards modelling were used to identify factors associated with AF and its relation with clinical outcomes. Setting: ACS complicated by AF. Patients: 120 566 patients with STEMI and NSTE-ACS in 10 clinical trials. Interventions: None evaluated. Main outcome measure: Short- and long-term mortality. Results: Occurrence of AF was 7.5% in the overall population (STEMI 8.0% (n = 84 161); NSTE-ACS = 6.4% (n = 36 405)). Seven-day mortality was higher for patients with AF (5.1%) than for those without (1.6%). After adjusting for confounders, association of AF with 7-day mortality was present in STEMI (hazards ratio (HR) = 1.65; 95% CI 1.44 to 1.90) and NSTE-ACS (HR = 2.30; 95% CI 1.83 to 2.90; p interaction = 0.015). Risk of long-term mortality (day 8 to 1 year) was also higher in STEMI (HR = 2.37; 95% CI 1.79 to 3.15) and NSTE-ACS (HR = 1.67; 95% CI 1.41 to 1.99). AF had a larger impact in NSTE-ACS on risk of short-term mortality (p<0.001), stroke (p<0.001), ischaemic stroke (p<0.001) and moderate or severe bleeding (p<0.001). Conclusions: AF is more common in patients with STEMI. An association of AF with short- and long-term mortality among patients with STEMI and NSTE-ACS was found. Understanding these findings may lead to better care of patients with this common arrhythmia.